2004
DOI: 10.1002/cncr.20187
|View full text |Cite
|
Sign up to set email alerts
|

Soluble vascular endothelial growth factor receptor 1, and not receptor 2, is an independent prognostic factor in acute myeloid leukemia and myelodysplastic syndromes

Abstract: BACKGROUND Vascular endothelial growth factor (VEGF) and its receptors (VEGFRs) are major regulators of angiogenesis, which plays a key role in the growth and dissemination of solid tumors and hematologic neoplasms. METHODS The authors measured the plasma concentrations of soluble VEGFR1 (sVEGFR1) and sVEGFR2 in 133 patients with acute myeloid leukemia (AML) and in 80 patients with myelodysplastic syndromes (MDS) at the time of initial presentation and compared clinical behaviors. RESULTS A reverse correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…In particular, sVegFr-1 has been studied, not only as a potential surrogate marker for disease progression, but also as a potential inhibitor of tumor angiogenesis in various types of cancers (5,31). Previous studies have shown that sVEGFR-1 and/or sVegFr-2 levels in plasma were higher in cancer patients than in healthy volunteers (21,32,33). our present data also demonstrated that plasma sVegFr-1 and sVegFr-2 levels of advanced CRC patients are significantly higher than those of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, sVegFr-1 has been studied, not only as a potential surrogate marker for disease progression, but also as a potential inhibitor of tumor angiogenesis in various types of cancers (5,31). Previous studies have shown that sVEGFR-1 and/or sVegFr-2 levels in plasma were higher in cancer patients than in healthy volunteers (21,32,33). our present data also demonstrated that plasma sVegFr-1 and sVegFr-2 levels of advanced CRC patients are significantly higher than those of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al also reported that plasma sVegFr-1, but not sVegFr-2, was an independent prognostic factor in AMl and myelodysplastic syndromes (21). little is currently known regarding the potential of plasma sVegFr-1 and sVegFr-2 levels as a predictive biomarker for treatment response and survival in crc patients treated with bevacizumab-based therapy.…”
Section: Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of the relationship between circulating sVEGFR-1 levels and preeclampsia reported that increased sVEGFR-1 is significantly associated with the development of preeclampsia, suggesting that immunodetectable sVEGFR-1 is biologically active (Levine et al, 2004). Regarding malignancies such as brain tumours or leukaemia, it was also documented that intratumoral or plasma sVEGFR-1 level is related to tumour phenotype or prognosis, suggesting that sVEGFR-1 plays a significant biological role not only during development or pregnancy but also in neoplasms (Lamszus et al, 2003;Hu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have investigated the potential of sVEGFR2 as a surrogate for tumor progression in melanoma, 25 myelodysplastic syndromes, or in various leukemias. 26 Although there is no information related to the utility of monitoring sVEGFR-2 levels in filarial infections, the inverse relationship between sVEGFR-2 and VEGF-A or VEGF-C is similar to that seen in other conditions. [27][28][29] Similarly, increased levels of VEGF and reduced levels of sVEGFR-2 have been shown with the use of inhibitors of cellular VEGF receptor tyrosine kinases VEGF RTKs, including sunitinib, 30 axitinib, 31 and telatinib, 32 suggesting a receptor downregulation-mediated increase in sVEGFR-2.…”
Section: Discussionmentioning
confidence: 98%